Kiko’s Anxiety In Akemi Dawn Bowman’s Starfish - Seda, Kresenstia Heldiana; Supsiadji, Mateus Rudi (CV. Era Digital Nusantara, 2023)
This article aims to discuss the issue of anxiety in Akemi Dawn Bowman's Starfish. The objectives of this study are to find the causes, effects, and types of anxiety experienced by the main character in the story. This study uses the psychoanalysis theory by Sigmund Freud to analyze Kiko's anxiety. The research method applied in this study is qualitative, with a psychology of literature approach. From the results of the analysis, there are four causes of the anxiety experienced by Kiko. The first is an experience that happens to Kiko in the past, caused by her uncle. The second is the conflict between Kiko and her mother. The third is Kiko’s environment, and the last is frustration. The effects of Kiko's anxiety are emotional effect and social anxiety. This can be seen from her feelings of anger because of the dispute that occurs between Kiko and her mother. Therefore, it can be concluded that Kiko's anxiety is categorized as neurotic and realistic anxiety. Neurotic anxiety comes from the id, which is an unconscious feeling so that it often loses its emotions such as sadness, anger, panic, and so on. Realistic anxiety occurs when there is a sense of fear of approaching danger.